2011
DOI: 10.1128/aac.01498-10
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Old World Cutaneous Leishmaniasis Caused by Leishmania infantum with Posaconazole

Abstract: Old World cutaneous leishmaniasis is a widespread and potentially disfiguring protozoal infection that is endemic in the Mediterranean basin, Africa, and parts of Asia. Human infection is caused by several species of Leishmania parasites, such as Leishmania infantum. Available systemic and topical treatments vary in efficacy and are often unjustified due to their toxicity. We report on a case that was treated with posaconazole, a drug typically considered an antifungal agent but which also targets specific met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Posaconazole is structurally similar to itraconazole, has an extended range of antifungal activity, and superior pharmacokinetic properties, but its oral bioavailability is extremely variable (46). Both posaconazole and itraconazole have been demonstrated effective against cutaneous leishmaniasis in several human clinical trials (12)(13)(14). Recently, our group showed the potent in vitro effects of itraconazole and posaconazole against Leishmania amazonensis (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posaconazole is structurally similar to itraconazole, has an extended range of antifungal activity, and superior pharmacokinetic properties, but its oral bioavailability is extremely variable (46). Both posaconazole and itraconazole have been demonstrated effective against cutaneous leishmaniasis in several human clinical trials (12)(13)(14). Recently, our group showed the potent in vitro effects of itraconazole and posaconazole against Leishmania amazonensis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the potent effects of different ergosterol biosynthesis inhibitors (EBIs) on these microorganisms, as these agents interfere with some essential steps in the ergosterol biosynthesis pathway (10). Itraconazole (ITZ) and posaconazole (POSA), two well-known azoles that inhibit the enzyme sterol C-14␣-demethylase (CYP51) and are frequently used as antifungal agents, also have effects in vitro and in vivo against trypanosomatids, including organisms from the Leishmania and Trypanosoma genera (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Recently, we demonstrated that ITZ and POSA have a potent effect against L. amazonensis, inhibiting its growth, disrupting mitochondrial function, and affecting the ultrastructure of several organelles (17).…”
mentioning
confidence: 99%
“…Amiodarone, a commonly used antiarrhythmic, has recently emerged as a potential drug candidate for the treatment of Chagas' disease, either as monotherapy or in combination with other drugs such as the azole-based antifungals posaconazole (4) and itraconazole (19). Nevertheless, and mainly due to the presence of a 2,5-diiodophenyl moiety in its structure, amiodarone exhibits a spectrum of undesirable side effects, causing mainly thyroid, gastrointestinal, and pulmonary toxicity, as well as less toxic side effects such as cutaneous pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also found that the combination of amiodarone with posaconazole, another potential option for treating Chagas' disease already in final clinical trials (24), and with other analogs has potent synergistic effects (4). Posaconazole has recently been found to effect successful treatment in humans with T. cruzi infection (20), and also in a case of cutaneous leishmaniasis (19).…”
mentioning
confidence: 99%
“…Efforts are also focused on developing novel drugs by using different strategies, from highthroughput screening for the identification of new targets to the characterization of already marketed drugs that display activity not only against their specific target but also against Leishmania parasites (Benaim et al, 2013(Benaim et al, , 2014De Menezes et al, 2015;Paniz Mondolfi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%